bFGF and SDF-1α Improve In Vivo Performance of VEGF-Incorporating Small-Diameter Vascular Grafts - Larisa Antonova; Anton Kutikhin; Viktoriia Sevostianova; Elena Velikanova; Vera Matveeva; Tatiana Glushkova; Andrey Mironov; Evgeniya Krivkina; Amin Shabaev; Evgeniya Senokosova; Leonid Barbarash (MDPI AG, 2021)
Tissue-engineered vascular grafts are widely tested as a promising substitute for both arterial bypass and replacement surgery. We previously demonstrated that incorporation of VEGF into electrospun tubular scaffolds from poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/poly(ε-caprolactone) enhances formation of an endothelial cell monolayer. However, an overdose of VEGF can induce tumor-like vasculature; thereby, other bioactive factors are needed to support VEGF-driven endothelialization and successful recruitment of smooth muscle cells. Utilizing emulsion electrospinning, we fabricated one-layer vascular grafts with either VEGF, bFGF, or SDF-1α, and two-layer vascular grafts with VEGF incorporated into the inner layer and bFGF and SDF-1α incorporated into the outer layer with the following structural evaluation, tensile testing, and in vivo testing using a rat abdominal aorta replacement model. The latter graft prototype showed higher primary patency rate. We found that the two-layer structure improved surface topography and mechanical properties of the grafts. Further, the combination of bFGF, SDF-1α, and VEGF improved endothelialization compared with VEGF alone, while bFGF induced a rapid formation of a smooth muscle cell layer. Taken together, these findings show that the two-layer structure and incorporation of bFGF and SDF-1α into the vascular grafts in combination with VEGF provide a higher primary patency and therefore improved in vivo performance.